PENDEKATAN HEART FRAMEWORK DALAM MENGANALISIS USER EXPERIENCE PADA APLIKASI HALODOC - Penengah, Pita; Daniati, Erna (Prosiding Seminar Nasional Teknologi dan Sistem Informasi, 2025)
This study aims to analyze the user experience of the Halodoc application using the HEART Framework, which measures five key dimensions of user experience: Happiness, Engagement, Adoption, Retention, and Task Success. A quantitative survey with a Likert-scale questionnaire was conducted among 55 active Halodoc users. The data were descriptively analyzed to evaluate user satisfaction, usage frequency, ease of feature adoption, user loyalty, and the effectiveness of the application in completing key tasks such as doctor consultations and medicine purchases. The results indicate that three dimensions — Happiness (81.1%), Adoption (81.4%), and Task Success (80.1%) — met the target threshold of 80%, while Engagement (71.1%) and Retention (78.5%) fell short. These findings suggest a need to enhance user engagement and retention by developing interactive features and retention strategies. The HEART Framework approach provides a comprehensive overview of the user experience quality of the Halodoc application and offers improvement recommendations to support more responsive, user-centered digital healthcare services.